Hedgehog/GLI signaling in hematopoietic development and acute myeloid leukemia—From bench to bedside - Tesanovic, Suzana; Krenn, Peter W.; Aberger, Fritz (Frontiers in Cell and Developmental Biology, 2022)
While the underlying genetic alterations and biology of acute myeloid leukemia (AML), an aggressive hematologic malignancy characterized by clonal expansion of undifferentiated myeloid cells, have been gradually unraveled in the last decades, translation into clinical treatment approaches has only just begun. High relapse rates remain a major challenge in AML therapy and are to a large extent attributed to the persistence of treatment-resistant leukemic stem cells (LSCs). The Hedgehog (HH) signaling pathway is crucial for the development and progression of multiple cancer stem cell driven tumors, including AML, and has therefore gained interest as a therapeutic target. In this review, we give an overview of the major components of the HH signaling pathway, dissect HH functions in normal and malignant hematopoiesis, and specifically elaborate on the role of HH signaling in AML pathogenesis and resistance. Furthermore, we summarize preclinical and clinical HH inhibitor studies, leading to the approval of the HH pathway inhibitor glasdegib, in combination with low-dose cytarabine, for AML treatment.